Dampak Pengembangan Desa Wisata Pada Peningkatan Kesejahteraan Masyarakat Desa Pearung Kecamatan Paranginan Kabupaten Humbang Hasundutan - Geopani Pakpahan; Randa Putra Kasea Sinaga; Husni Thamrin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The tourism sector is a potential sector to be developed as a source of local revenue. With the development of a tourist village, it will have an impact on the welfare of the surrounding community. The purpose of this study is to describe and analyze the impact of the development of Pearung Tourism Village on the welfare of the surrounding community. This research uses a qualitative approach and descriptive research type. The research location was in Pearung Tourism Village, Paranginan Sub-district, Humbang Hasundutan Regency. The results of this study show that the impact of the development of Pearung Tourism Village is the impact on the environment and social, as well as the economic impact. The impact on the environment is the cleanliness that is maintained and the state of the surrounding environment that is maintained. The social impact felt is the cooperation between residents to jointly protect the surrounding environment. The economic impact is that with the development carried out, it can provide the surrounding community with new job opportunities so as to increase community income. Some people who previously did not have jobs also now have jobs so that they can improve their standard of living.